Epithelioid angiosarcoma arising in a uterine leiomyoma with associated elevated CA-125: A case report - Sarah V. Strickland; Mark R. Kilgore; Elise J. Simons; Mara H. Rendi (Elsevier, 2017)
We describe the case of a 67 year old female with longstanding uterine leiomyomas who presented with fatigue, weight loss, elevated CA-125 and an enlarging mass arising from the posterior uterine fundus. Histologic sections of the mass contained a leiomyoma with interspersed foci of malignant epithelioid cells forming anastomosing vascular channels. The neoplastic cells were diffusely positive for CD31 and FLI1, supporting the morphologic impression of epithelioid angiosarcoma. Few cases of epithelioid angiosarcoma arising within a leiomyoma have been described. In this report we discuss this association and describe its relation with elevated CA-125.